2014
DOI: 10.1109/lwc.2014.2356203
|View full text |Cite
|
Sign up to set email alerts
|

Energy-Efficient Base Station Deployment in Heterogeneous Networks

Abstract: In underlay heterogeneous networks (HetNets), the distance between a macro base station (MBS) and a macro user (MU) is crucial for a small-cell based station (SBS) to control the interference to the MU and achieve the coexistence. To obtain the distance between the MBS and the MU, the SBS needs a backhaul link from the macro system, such that the macro system is able to transmit the information of the distance to the SBS through the backhaul link. However, there may not exist any backhaul link from the macro s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
26
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 16 publications
0
26
0
Order By: Relevance
“…Node deployment problems also appear in the context of cellular networks [9]- [11]. Coskun et al [9] analyze the BS deployment in heterogeneous cellular networks including macro and micro BSs.…”
Section: Related Work and Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Node deployment problems also appear in the context of cellular networks [9]- [11]. Coskun et al [9] analyze the BS deployment in heterogeneous cellular networks including macro and micro BSs.…”
Section: Related Work and Applicationsmentioning
confidence: 99%
“…The corresponding average distortion is the total channel capacity divided by the total power and the corresponding constraint requires a capacity threshold. In [9], a greedy algorithm is proposed to optimize the micro BS deployment. Zhang et al [10] consider a multi-tier cellular network where BSs are placed in multiple tiers.…”
Section: Related Work and Applicationsmentioning
confidence: 99%
“…To lower the consumption, it is found that an improved and efficient deployment of SCs must be taken into consideration for economical and environmental advantages. Several solutions and strategies related to improvements of energy efficiency such as change in BS hardware, heterogeneous deployments, resource management, and network deployments are proposed . In Reference , authors have presented the effect on power consumption in heterogeneous cellular network with MCs and varying SCs.…”
Section: Introductionmentioning
confidence: 99%
“…As regards to AP selection, a range of sophisticated strategies have been conceived for large-scale wireless access networks relying for example on game theory [11], [12], on price theory [13], [14], on Markov decision processes (MDP) [15], etc. Most of them aim for balancing the traffic load of the APs, as well as for providing an improved QoS [16], [17], [18].…”
Section: Introductionmentioning
confidence: 99%